Enron The tale less trumpeted [management]. - Teitelman, R.
There are at least two stories of Enron Corp. First is the business story: Houston-based energy giant takes a big (and mysterious) charge, raising questions about its accounting. Its lenders yank their lines of credit, the company collapses, and the massive problem of reorganizing its tangled and far-flung affairs begins. Then there's the scandal. This is a complex and still unfolding story, replete with document shredding, political donations, phone calls to administration officials, unloading of shares by senior executives, an apparent suicide, and charges of accounting fraud stemming from a bewildering array of off-balance sheet entities with curious names. In this paper, the author details hoe the blame falls not just on faulty bookkeeping and inflated expectations, but also on a fashionable but questionable model of stewardship.
Keywords: Enron Corporation; USA; Accounting; Energy company; Fraud; Management; Scandal; Stewardship